ANALISIS STRATEGI PROMOSI BISNIS DALAM MENINGKATKAN VOLUME PENJUALAN DI TOKO AL-FIRDAUS PONDOK PESANTREN SYAICHONA MOH. CHOLIL BANGKALAN - Rahmat; Sabil, Afif (Al-Idarah, 2023)
Sale is a type of activity that aims to develop various plans that lead to business activities to meet the needs and desires of buyers or consumers to generate profits. A company will profit greatly if the sales volume obtained is more significant and vice versa. The type of research in this study is a type of qualitative research, the data sources in this study consist of secondary and primary data. The data collection techniques used were observation, interviews and documentation. The data analysis used in this study was non-statistical or did not involve numbers/formulas but describing them in writing and reflections. In this study, it can be concluded that the business promotion strategy is increasing sales volume at the Al-Firdaus Pondok Pesantren Syaichona Moh. Cholil applies four patterns of a business promotion strategy, namely face-to-face promotion, advertising promotion, publicity promotion and sales promotion. Business promotion strategy for the Al-Firdaus Shop Islamic Boarding School Syaichona Moh. Cholil has complied with the provisions of Islamic Economics.